The Role of Entrepreneurs, Management and Intellectual Property Rights in Improving Micro Business Competitiveness in Rancatungku Village - Sugiartiningsih Sugiartiningsih; Suparjiman; Rizky Dwi Larasati; Septian Yunianto; Khaerani Arum Kanti (Faculty of Economics Universitas Sarjanawiyata Tamansiswa, 2023)
ABSTRACT Purpose - The purpose of Community Service (PKM) is for a workshop on the role of entrepreneurship, management and registration of Intellectual Property Rights (HKI) in increasing the competitiveness of micro-enterprises in Rancatungku village. Methods - The workshop method begins with a preliminary survey, observations of business houses, interviews with micro-enterprises, licensing arrangements, and preparation of presenters. Result and discussions - The workshop was held in the Rancatungku village hall on February 27, 2022, which was attended by Micro Business actors, especially those engaged in the culinary field such as pastries and sponge cakes. The workshop program is divided into three, namely enlightenment on the importance of entrepreneurship for micro-enterprises; introduction of management aspects from production, packaging, transformation technology in marketing culinary products, external capital and recognition of production ownership. Conclusions - The result of PkM activities is their high interest in being given training on packaging, branding and marketing in subsequent PkM activities so that they can penetrate supermarkets and have high purchasing power across countries. Keywords: entrepreneurship, management, intellectual property rights